Evaluation of the Performance of the Malang City Regional Government in the Implementation of the Government Agency Performance Accountability System (SAKIP) - Dika Putra Wijaya; Nur Laila; Wirda Amirotul Amiroh (Journal Governance Society, 2025)
This study evaluates how the Malang City Government integrates accountability-based governance and sustainable development within the implementation of the Government Agency Performance Accountability System (SAKIP) in 2024. The study aims to (1) assess the effectiveness of SAKIP and the Electronic-Based Government System (SPBE) in strengthening governance performance, (2) analyze their linkage with key social, economic, and environmental outcomes, and (3) formulate an integrated interpretation of Malang City’s 2024 performance as a model of sustainable urban governance. A qualitative descriptive design with systematic document analysis was employed, drawing on the 2024 Government Agency Performance Report (LKjIP), the Local Government Implementation Report (LPPD), the 2024 AKIP Evaluation Report, regional development plans and complementary statistical and regulatory sources. The findings show that Malang’s performance achievement reached 101.51%, with a SAKIP score of 81.8 and an SPBE index of 4.24, accompanied by an increase in the Human Development Index to 83.42, economic growth of 5.93%, and an Environmental Quality Index of 61.76, supported by innovations in creative economy development, human resource improvement, digital public services, and community-based environmental management. The study concludes that the synergy between accountability instruments, digital transformation, and sustainability-oriented policies has positioned Malang City as a promising model of integrated urban governance, while highlighting remaining challenges related to digital inclusion, fiscal capacity, and long-term impact measurement that must be addressed to secure more equitable and resilient development in the future.